2012
DOI: 10.1038/mp.2012.157
|View full text |Cite
|
Sign up to set email alerts
|

Common variant at 16p11.2 conferring risk of psychosis

Abstract: Epidemiological and genetic data support the notion that schizophrenia and bipolar disorder share genetic risk factors. In our previous genome-wide association (GWA) study, meta-analysis and follow-up (totaling as many as 18,206 cases and 42,536 controls), we identified four loci showing genome-wide significant association with schizophrenia. Here we consider a mixed schizophrenia and bipolar disorder (psychosis) phenotype (addition of 7,469 bipolar disorder cases, 1,535 schizophrenia cases, 333 other psychosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 49 publications
1
69
0
1
Order By: Relevance
“…deCODE has genotyped 100,373 Icelandic subjects using microarrays from Illumina (Human317K and larger). This includes 708 schizophrenia patients (2 deletion carriers), 1,136 bipolar patients (2 deletion carriers), 507 autistic individuals (1 deletion carrier) and 98,022 controls (37 deletion carriers), which were described previously Steinberg et al, 2014;Vassos et al, 2012;Rujescu et al, 2009;Weiss et al, 2008). CNV analysis of the ULK4 region was performed by interrogation of chip data spanning exons of ULK4.…”
Section: Cnv Analysesmentioning
confidence: 99%
“…deCODE has genotyped 100,373 Icelandic subjects using microarrays from Illumina (Human317K and larger). This includes 708 schizophrenia patients (2 deletion carriers), 1,136 bipolar patients (2 deletion carriers), 507 autistic individuals (1 deletion carrier) and 98,022 controls (37 deletion carriers), which were described previously Steinberg et al, 2014;Vassos et al, 2012;Rujescu et al, 2009;Weiss et al, 2008). CNV analysis of the ULK4 region was performed by interrogation of chip data spanning exons of ULK4.…”
Section: Cnv Analysesmentioning
confidence: 99%
“…Detailed information on each sample, including diagnostic assessment, genotyping, quality control and association analysis has been published previously. 11,12,15,[42][43][44] Briefly, the five samples included in replication study are: (1) Genetic association analysis between SNPs in CAMKK2 gene and schizophrenia susceptibility…”
Section: Case-control Subjectsmentioning
confidence: 99%
“…During the past few decades, genetic analyses including genome-wide association studies (GWAS) have identified a wealth of risk loci for SCZ and BPD in diverse populations [4][5][6][7][8]. Meanwhile, studies considering SCZ and BPD as a single major psychosis phenotype revealed shared risk alleles [9][10][11][12] and an overlapping polygenic component [13,14]. These data are consistent with current clinical and epidemiological analyses, which predict substantial overlap of risk factors and genetic predisposition between SCZ and BPD [3].…”
Section: Introductionmentioning
confidence: 99%